Evaluation of the Combined Effects of Heat and Lighting on the Level of Attention and Reaction Time: Climate Chamber Experiments in Iran - Zohreh Mohebian; Somayeh Farhang Dehghan; Habiballah Dehghan (The Scientific World Journal)
Heat exposure and unsuitable lighting are two physical hazardous agents in many workplaces for which there are some evidences regarding their mental effects. The purpose of this study was to assess the combined effect of heat exposure and different lighting levels on the attention rate and reaction time in a climatic chamber. This study was conducted on 33 healthy students (17 M/16 F) with a mean (±SD) age of 22.1±2.3 years. The attention and reaction time test were done by continuous performance test and the RT meter, respectively, in different exposure conditions including the dry temperatures (22°C and 37°C) and lighting levels (200, 500, and 1500 lux). Findings demonstrated that increase in heat and lighting level caused a decrease in average attention percentage and correct responses and increase in commission error, omission error, and response time (P<0.05). The average of simple, diagnostic, two-color selective, and two-sound selective reaction times increased after combined exposure to heat and lighting (P<0.05). The results of this study indicated that, in job task which requires using cognitive functions like attention, vigilance, concentration, cautiousness, and reaction time, the work environment must be optimized in terms of heat and lighting level.